SARS‐CoV‐2 infections in pediatric patients: A comparison of three pandemic waves. (25th January 2022) - Rovida, Francesca; Giardina, Federica; Ferrari, Guglielmo; Paolucci, Stefania; Piralla, Antonio; Baldanti, Fausto
Abstract: The pediatric population seems to be at a lower risk of developing severe clinical symptoms of COVID‐19. However, the clinical and epidemiological characteristics of COVID‐19 in children are yet to be fully clarified. This retrospective observational study aimed to evaluate the frequency of pediatric laboratory‐confirmed COVID‐19 patients from February 2020 to April 2021. A total of 740 (5.1% of total) pediatric COVID‐19 cases were observed during the study period. The peak of pediatric cases was observed in November 2020, with 239 cases. During the first wave of pandemics, the frequency of pediatric cases was 0.89% (49/5877 cases), ranging from 0.6% in February 2020 to 1.3% in April 2020. On the contrary, after the beginning of the second wave, the frequency of pediatric cases raised from 5.3% in September 2020 to 9.4%in February 2021, with an overall frequency of 8.2% (690/8416 cases). A different rate of SARS‐CoV‐2 circulation was observed among the pediatric population between the pandemic waves. During the second wave, two peaks of cases were observed. The last peak was associated with the spread of a more transmissive SARS‐CoV‐2 strain (VOC 202012/01).